PRODUCTIVITY AND COST ANALYSIS OF FELLING AND BUCKING OF TEAK TREES (Tectona grandis L.F.) USING REDUCED IMPACT LOGGING (RIL) TECHNIQUE IN TELAWA FOREST MANAGEMENT UNIT, CENTRAL JAVA: Produktivitas Dan Analisis Biaya Penebangan Serta Pembagian Batang Tegakan Jati (Tectona grandis L.F.) di RPH Ngaren, BKPH Kedungcumpleng, KPH Telawa - Waryanti, Putri; Rahmadwiati, Rissa; Agustina, Ana (Jurnal Penelitian Hasil Hutan, 2025)
Forest harvesting activities are forest management activity which aims to increase forest value, obtain forest products needed by the community, and provide employment opportunities for communities around the forest. One of the forest products in Java Island that is widely used because of its advantages is teak wood (Tectona grandis L.f.). One of the KPHs that produces teak wood is KPH Telawa Perum Perhutani. The implementation of Reduced Impact Logging (RIL) techniques is expected to increase productivity and obtain optimal results, as well as realizing sustainable forest management. This research aims to calculate the productivity and costs required for felling and bucking activities. Sampling was carried out using a purposive sampling method with the criteria of teak stands in the same age class at RPH Ngaren, BKPH Kedungcumleng, KPH Telawa. Data was obtained by measuring 36 samples of homogeneous teak stands in age class V and the same diameter class. Measuring working time uses the cumulative method. The research results show that the effective productivity of cutting and dividing stems in the Ngaren RPH is 1.80 m3/hour. The results of the regression analysis show that volume and effective time have a significant influence on felling and felling productivity. Volume is directly proportional to productivity while working time is inversely proportional to productivity. Cost analysis includes fixed and variable costs to obtain IDR 34,120.08/m3 results.